Autoimmune thyroid disease and myasthenia gravis: a study bidirectional Mendelian randomization - Wang, Suijian; Wang, Kui; Chen, Xiaohong; Chen, Daiyun; Lin, Shaoda (Frontiers in Endocrinology, 2024)
Previous studies have suggested a potential association between AITD and MG, but the evidence is limited and controversial, and the exact causal relationship remains uncertain.Therefore, we employed a Mendelian randomization (MR) analysis to investigate the causal relationship between AITD and MG. 2 Methods To explore the interplay between AITD and MG, We conducted MR studies utilizing GWAS-based summary statistics in the European ancestry.Several techniques were used to ensure the stability of the causal effect, such as random-effect inverse variance weighted, weighted median, MR-Egger regression, and MR-PRESSO. Heterogeneity was evaluated by calculating Cochran's Q value. Moreover, the presence of horizontal pleiotropy was investigated through MR-Egger regression and MR-PRESSO Results